Self-determination and the limits on the right to include - Erez, L; Banai, A (SAGE Publications, 2024)
States’ right to exclude prospective members is the subject of a fierce debate in political theory, but the right to include has received relatively little scholarly attention. To address this lacuna, we examine the puzzle of permissible inclusion: when may states confer citizenship on individuals they have no prior obligation to include? We first clarify why permissible inclusion is a puzzle, then proceed to a normative evaluation of this practice and its limits. We investigate self-determination – a dominant principle in theories of the right to exclude – as a normative ground for limits on the right to include. We argue that states' duties to respect one another's self-determination yields limits on permissible inclusion. When inclusive policies for citizenship undermine the permissible scope of self-determination of other states, they are impermissible; they should either be prohibited or compensated for.